Electronystagmography/videonystagmography (ENG/VNG) - McCaslin, Devin L. (San Diego c)
"In order to provide a foundation for understanding ENG/VNG test results, the early sections of the text are dedicated to a description of normal and impaired peripheral and central vestibular system function. Also addressed is the process of central nervous system compensation. These sections are followed by a description and interpretation of the ENG/VNG subtests including: an expanded ocular motor testing section, positional/ing testing, and caloric testing. The text now also includes a chapter describing the most common disorders causing dizziness and provides the diagnostic criterion for each. Finally, examples of counseling materials and illustrative case studies that serve to highlight the principles and techniques covered in the manual are provided"--
Neural Control of Eye Movements -- Anatomy and Physiology of the Vestibular System -- Pretest Procedures for VNG -- Eye Movement Examination -- Positional Testing -- The Caloric Test -- Common Vestibular Disorders: Clinical Presentation
Preceded by ENG/VNG / Devin L. McCaslin. c2013.
Keywords: Audiology